(untitled) (Al-Qamar, 2022)
The long-running debate over Islam and democracy has struck a watershed moment. Since the outbreak of the Political upheavals in late 2010, political Islam and democracy have been closely associated. The question of whether they are interoperable is now mostly moot. Neither of them can now operate without the other. On 14th of august 1947 Pakistan was emerged on the map of the world as an Islamic democratic state but the dream of its founder could not become true and it had to face autocratic and non-democratic traditions. After a long struggle democracy was rstored under Muhammad Khan Juneju but could not established its roots and had to face the wrath of military dictator. This article will highlight the background of the struggle for democracy and the style of government of Juneju which eventually faced the music of COAS Zia Ul Haq.